Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Review: 28

Answer

$\dfrac{9x+7}{6x^{2}}-\dfrac{3x+4}{6x^{2}}=\dfrac{2x+1}{2x^{2}}$

Work Step by Step

$\dfrac{9x+7}{6x^{2}}-\dfrac{3x+4}{6x^{2}}$ Evaluate the substraction: $\dfrac{9x+7}{6x^{2}}-\dfrac{3x+4}{6x^{2}}=\dfrac{(9x+7)-(3x+4)}{6x^{2}}=...$ $...=\dfrac{9x+7-3x-4}{6x^{2}}=\dfrac{6x+3}{6x^{2}}=...$ Take out common factor $3$ from the numerator and simplify: $...=\dfrac{3(2x+1)}{6x^{2}}=\dfrac{2x+1}{2x^{2}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.